Development of Color Blindness Test Application Using Ishihara Template at Rumbai Public Health Center - Memen Akbar; Warnia Nengsih Sikumbang; Wiwin Styorini (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2022)
This research addresses the problem of color blindness testing at Puskesmas Rumbai which serves color blindness checks using printed books. The colors in the book became less clear as time went on. Therefore, this research makes a digital color blindness examination as part of the application for obtaining a certificate of health. The resulting application is named SIP SEHAT which stands for Aplikasi Pelayanan Surat Keterangan Kesehatan. This application was developed using prototyping method approach. There are 3 categories of users of this application, namely the registration section, doctor or nurse, and administration section. The registration section inputs the identity of the patient who will perform the examination. Meanwhile, doctors or nurses carry out examinations and medical examinations of patients who come. Color blindness test is one of the features found in doctors or nurses. Patients independently answer 24 Ishihara templates that appear on the application. Based on the answers from the patient, the application will display the color blindness test results, whether including total color blindness, partial color blindness, or not color blindness. The administration section prints a certificate of a patient who has performed an examination and gets a recapitulation of health examination reports per month. The application has been tested with 3 types of testing, namely accuracy testing, correctness testing, and usability testing. Based on these three tests, it can be concluded that this application is ready for use by the Puskesmas Rumbai to serve the processing of certificates of health. Based on service process analysis, this application makes the process of managing a health certificate making more efficient by 42.86%.